Nanotechnology. - Charles F. Huber (Issues in Science and Technology Librarianship)
Nanotechnology is a hot topic in most science and technology libraries. The literature of nanotechnology is widely scattered across traditional disciplines. This paper provides an introduction for the non-expert to key terminology, reference works and indexes to the literature of nanotechnology. [ABSTRACT FROM AUTHOR]